Incorporating Financial Stability in Inflation Targeting Frameworks - Aydin, Burcu (IMF Working Papers; Working Paper, 2011)
The global financial crisis has exposed the limitations of a conventional inflation targeting (IT) framework in insulating an economy from shocks, and demonstrated that its rigid application may aggravate the effect of shocks on output and inflation. Accordingly, we investigate possible refinements to the IT framework by incorporating financial stability considerations. We propose a small open economy DSGE model, calibrated for Korea during the period of 2003 - 07, with real and financial frictions. The findings indicate that incorporating financial stability considerations can help smooth business cycle fluctuations more effectively than a conventional IT framework.